Endometrial biopsy using a novak curette for the detection of endometrial pathology - Esteban-Habana, Ma. Antonia
Various methods have been developed to assess the presence of endometrial pathology in women with abnormal uterine bleeding. The use of curettage as the standard method of endometrial sampling is questioned. Endometrial biopsy is a safe alternative and the accuracy of biopsy using the novak curette is evaluated. The objectives of this study: 1. To determine the adequacy of specimens obtained from endometrial biopsy and curettage. 2. To determine the sensitivity, specificity, predictive values, accuracy and likelihood ratios of histology results obtained from endometrial biopsy with those obtained from curettage. 3. To determine the sensitivity, specificity, predictive values, accuracy and likelihood ratios of histology results obtained from endometrial biopsy and curettage with those obtained from available hysterectomy specimens. 4. And to compare adverse events and any difficulties encountered in both techniques. Criterion validation study done prospectively where endometrial biopsy was evaluated using an independent and blind comparison with a gold standard, the histology result from an endometrial curettage and when available, the hysterectomy specimen. The study was approved by the Committee on Research Implementation and Development of the College of Medicine and the Philippine General Hospital of the University of the Philippines. It was conducted at the Outpatient Section of the Department of Obstetrics and Gynecology of the Philippine General Hospital from June 1, 1998 to June 7, 1999. Four hundred thirty one consecutive patients with clinical indications for curettage who satisfied the following inclusion and exclusion criteria were included in the study.